ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIKA DAN METAKOGNITIF SISWA SELAMA PANDEMI COVID-19 DI SMA NEGERI 1 ANDAM DEWI - Mei Kristina Situmorang; Muhammad Syahril Harahap; Marzuki Ahmad (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to describe mathematic creative thinking ability and student’s metacognitive during Covid-19 pandemic in SMA Negeri 1 Andam Dewi. This research was conducted by applying descriptive quantitative method. Sample of this research is 20 students which taken by using cluster random sampling technique from 36 students. Questionnaire and test were used in collecting the data. Questionnaire sheet shows the average of students’ metacognitive is 78.61 (good category) and test sheet shows the average of mathematic creative thinking ability is 83.53 (high category). Futhermore by using ttest Kolmogorov- Sminov shows significant value is less than 0.05 (0.000<0.05). It means there is any significant influence of students’ metacognitive on mathematic creative thinking ability during Covid-19 pandemic in SMA Negeri 1 Andam Dewi.